A hybrid optimisation algorithm for production scheduling problem with random orders' arriving. Issue 4 (2017) - Li, Xixing; Du, Baigang; Guo, Shunsheng; Liu, Yi; Wang, Lei
Production scheduling problem is a very important functional optimisation problem in the modem manufacturing system and which greatly impacts the efficiency and capacity of the manufacturing system. It has been proved to be a NP-hard problem and cannot be well solved based on traditional algorithms. Therefore, it is very necessary to develop efficiency algorithms which can obtain a good production plan with approximate optimal solution in a reasonable time. In this paper, a new method based on integrated genetic algorithm and tabu search is proposed and which can feasibly balance the exploration ability and exploitation ability of calculation. Also, the solution encoding and decoding, crossover and mutation operator, tabu search strategies have been illustrated. In order to evaluate the performance of the proposed algorithm, one experiment has been carried out and the comparisons among them are also presented. The result shows that the proposed algorithm can obtain satisfactory solutions and also it is applied to solve the production scheduling problem in a practical textile machine manufacturing enterprise.